Editorial Ruminations: Publishing Kyklos - Bruno S. Frey; Reiner Eichenberger; Rene L. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2009)
Scholars today are under increasing pressure to publish in A-journals, the main role of which consists in certifying that a paper meets traditional academic standards. Consequences of this pressure are multiple authorship, slicing of ideas and incentives to deviate from the truth. The overburdended reviewers' evaluations are characterized by selfish efforts to protect their intellectual capital and to avoid risk. The behaviour of editors much depends on whether there are a large or small number of editors. The editors of Kyklos respond to these developments by welcoming innovative papers that go beyond standardized orthodoxy.
Keywords: A1; A20; B00; B40; D02; 330; Academic Publishing; Journals; Reviewers; Editors; Unorthodox Economics